L’application de la technique du jeu du Virelangue pour améliorer la prononciation du français des élèves de la classe XII du SMA N 2 Kudus - Siti Rofiah; Diah Vitri Widayanti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This study employs the tongue twister game technique to teach French pronunciation to students in Class XII at SMA N 2 Kudus. This study aims to describe (1) the application of the tongue twister game technique to practice French pronunciation, and (2) to find out whether the tongue twister game technique is efficacious in improving French pronunciation in class XII F11 SMA N 2 Kudus students. This research is a pre-experimental quantitative study, employing a One-Group Pretest-Posttest Design. The research instruments used tests and documentation. The sample used was class XII F-11, selected using a random sampling technique. The application of a tongue twister is done by dividing into several groups, then given a tongue twister with the help of cards. The average pretest score was 45.64, and the posttest score was 73.58. This indicates a difference in pronunciation between the pretest and posttest. The results of the effect size test with Cohen’s d formula of 2.019 show that the tongue twister has a substantial effect in improving the French pronunciation of students in class XII F-11 SMAN 2 Kudus.